Are Herbal Medicines Effective in the Treatment of Ischemic Stroke? A Systematic Review of Human-Controlled Clinical Trials - Elahe Delshad; Hassan Doosti; Guillemin GJ; Hamideh Naghedi-Baghdar; Zahra Ayati; Masoumeh Kaboli Farshchi; Roghayeh Javan; Mahdi Yousefi * (Lorestan University of Medical Sciences, 2019)
Cerebrovascular disorders are common diseases and stroke constitutes the third cause of death following myocardial infarction and cancer as well as the first cause of disability across the globe worldwide. Although several studies have demonstrated the beneficial effects of herbal preparations on stroke, this study was designed to classify and analyze the results of these studies. For this purpose, electronic databases were searched including Cochrane, ISI, PubMed, and Scopus to 15 January 2018 for English language human studies. Only randomized controlled trials (CRTs) were involved and case studies were excluded from this review. Finally, four randomized controlled trials were included in this systematic review which four medicinal plants were assessed in four articles. Inclusion and exclusion criteria, and also outcome measures varied between different articles. The results of these studies indicated that these special medicinal plants may be effective in the management of ischemic stroke and No severe reactions were described during the administration of herbal remedies. However, the efficacy of herbal medicines on Ischemic stroke needs to be further proven through future additional studies